Penentuan Tarif Tol Berdasarkan Analisis Kelayakan Finansial (Studi Kasus: Jalan Tol Pekanbaru-Minas) - Guspi, Guspi; Sandhyavitri, Ari; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Road side which connected Pekanbaru-Dumai is one of the most important transportation lane in Riau and was projected as over capacity road. Therefore, a highway design and planning needs to be done in order to overcome these problems. The construction of a highway needs a quite large investment according to feasibility study which came from private. In order to get on investment full cost recovery analysis on this project in essential. The full cost recovery analysis aims to analyse the finance appropriateness on the construction of Pekanbaru-Minas highway with the life span for 40 years. Analysis was done by assuming the traffic growth rate factor (i) 5% /year, bank interests 9,78% /year, inflation was calculated as 5,82% /year from the established fee, ie Rp 860,00 /km. Financial analysis results showed that investment in the development of highway Pekanbaru-Minas give Internal Rate of Return (IRR) result is 10.35%, Net Present Value (NPV) Rp 94.037.000.244,59, Benefit Cost Ratio (BCR) 1.063 and payback period for 26 years. According to this analysis, it could be concluded that the construction of Pekanbaru-Minas Highway is worthy to be proceeded. Keywords: Highway, Rate, Financial Properness